Navigating the Transition to a New Leadership Position: Moving on and Moving up - Luanne Thorndyke; Martha Grayson; Maryellen Gusic (Association of American Medical Colleges, 2014)
Abstract This leadership workshop addresses a leadership topic for which there is a paucity of information in the current literature: how to smoothly leave a position/organization and move effectively into a new position/organization. Thus, the purpose of this resource is to provide tools for a new or aspiring leader to enable him/her to strategically and successfully manage the transition to a new leadership role in a new organization. The workshop is specifically tailored to the leadership development of faculty in academic medicine. We utilize a case-based format to explore a real-world scenario that new leaders are likely to encounter. The case was developed from a compilation of the actual experiences of three leaders in academic medicine who, reflecting upon their own transitions to new, higher leadership positions in new institutions and their knowledge of the extant literature, created an illustrative case with essential content. The case study uncovers the major issues and opportunities facing a leader who is new to their position and/or the institution/organization. The workshop is organized into four sections or parts, presented as longitudinal "chapters" of the case. Questions at the end of each section allow workshop participants-new and aspiring leaders as well as more experienced leaders who have encountered similar situations-with an opportunity to share and learn from each other as well as from the workshop leader(s). For each section of the case, the core content of the section follows the section 'title slide" slide portraying the specific chapter of the case. We developed and implemented this interactive workshop with hands-on activities, in order to engage leaders in the reflective and proactive work required to achieve the goal of a smooth, efficient, and successful transition to a new leadership position. In order to reach a substantial number of new and aspiring leaders in academic medicine, the workshop was presented at the Annual Meeting of the Association of American Medical Colleges in a plenary session cosponsored by multiple stakeholder groups of the association. Approximately 100 individuals attended the session. Evaluations completed by participants documented the usefulness of the content and approach, and comments underscored the value perceived by participants.